Silencing RON Receptor Signaling Inhibits Growth and Sensitizes Pancreatic Cancer Xenografts to Gemcitabine - Logan-Collins, Jocelyn (2010)
The RON receptor tyrosine kinase is overexpressed in pancreatic intraepithelial neoplasia (PanIN) and the majority of pancreatic cancers. Exposure of cultured pancreatic cancer cells to RON ligand enhances migration/invasion and apoptotic resistance and RON was recently identified as a key effector of K-Ras signaling in pancreatic and lung cancer cells. The significance of RON overexpression in pancreatic cancer cells in vivo, however, remains unknown. In this study, we demonstrate that RON signaling mediates a unique transcriptional program that is conserved between cultured cells derived from murine PanIN and human pancreatic cancer cells grown as subcutaneous tumor xenografts. In both systems, RON signaling regulates expression of genes implicated in cancer cell survival including Bcl-2 and the transcription factors STAT-3, and c-jun. We further demonstrate that shRNA silencing of RON in pancreatic cancer xenografts inhibits their growth, primarily by increasing their susceptibility to apoptosis and sensitizes them to gemcitabine treatment. Finally, we show that escape from RON-silencing is associated with re-expression of RON and/or expression of phosphorylated forms of the related receptor c-met or the epidermal growth factor receptor. Taken together, these findings suggest that RON receptor signaling regulates pathways important for pancreatic cancer cell survival and resistance to gemcitabine in vivo and suggests mechanisms by which pancreatic cancer cells may circumvent RON-directed therapies.